The Value of Hard Work Embodied in the Novel Mata dan Manusia Laut by Okky Madasari - Luvi Kurnia Permana; Sarwiji Suwandi; Atikah Anindyarini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims at describing the character education values embodied in the novel Mata dan Manusia Laut by Okky Madasari. The novel is chosen due to the character values that can be a reflection of students to apply in daily life. As the object of the study is the stories of this novel which contains the character education values. This study is a descriptive qualitative research in which the data in this study are in the form of words. The data used in the form of a narrative dialogue between characters in the novel. The technique used is the content analysis method. For the data validity of this research uses theory triangulation, method triangulation, and data triangulation. The data analysis technique used is the analysis of the Flow model by Miles and Huberman (2012) through the stages of data reduction, data presentation, as well as withdrawal conclusions. The theory of character education values refers to the Thomas Lickona theory which consists of ten character education values. However, this study is more focused on the value of hard work. The results of this study show that regarding the character education values, novel Mata dan Manusia Laut by Okky Madasari gives examples as well as description especially for the value of hard work which contains eleven values quoted from the novel. Also, the novel Mata dan Manusia Laut by Okky Madasari is representative enough as literacy learning, especially for a novel containing character education.